An unusual hantavirus outbreak in southern Argentina: person-to-person transmission? Hantavirus Pulmonary Syndrome Study Group for Patagonia - Wells, Rachel M. (1997)
Fil: Wells, Rachel M. Centers for disease control and prevention; Georgia, Estados Unidos.